Integrated management of neonatal and childhood illness strategy in Zimbabwe: An evaluation. - Nigel James; Yubraj Acharya (Public Library of Science (PLoS), 2021)
More than five million children under the age of five die each year worldwide, primarily from preventable and treatable causes. In response, the World Health Organization's Integrated Management of Childhood Illnesses (IMNCI) strategy has been adopted in more than 95 low- and middle-income countries, 41 of them from Africa. Despite IMNCI's widespread implementation, evidence on its impact on child mortality and institutional deliveries is limited. This study examined the effect of IMNCI strategy in the context of Zimbabwe, where neonatal and infant mortality rates are among the highest in the world. We used binary logistic regression to analyze cross-sectional data from the 2015 Zimbabwe Demographic and Health Survey. Zimbabwe implemented the IMNCI strategy in 2012. Our empirical strategy involved comparing neonatal and infant mortality and institutional deliveries within the same geographic area before and after IMNCI implementation in a nationally representative sample of children born between 2010 and 2015. Exposure to IMNCI was significantly associated with a reduction in neonatal mortality (adjusted odds ratio (95% CI): 0.70 (0.50, 0.98)) and infant mortality (adjusted odds ratio (95% CI): 0.69 (0.54, 0.91)). The strategy also helped increase institutional deliveries significantly (adjusted odds ratio (95% CI): 1.95 (1.67, 2.28)). Further analyses revealed that these associations were concentrated among educated women and in rural areas.The IMNCI strategy in Zimbabwe seems to be successful in delivering its intended goals. Future programmatic and policy efforts should target women with low education and those residing in urban areas. Furthermore, sustaining the positive impact and achieving the child health-related Sustainable Development Goals will require continued political will in raising domestic financial investments to ensure the sustainability of maternal and child health programs.